2020
DOI: 10.1021/acs.jpcc.0c03713
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Doping in Group IV Hexagonal-Diamond-Type Crystals

Abstract: Over the last few years, group IV hexagonal-diamond type crystals have acquired great attention in semiconductor physics thanks to the appearance of novel and very effective growth methods. However, many questions remain unaddressed on their extrinsic doping capability and on how it compares to those of diamond-like structures. This point is here investigated through numerical simulations conducted in the framework of the Density Functional Theory (DFT). The comparative analysis for group III and V dopant atom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…, ref for a discussion of the case of H in SiC). Notice, however, that whenever we compare the formation energy of a given impurity in the ZB or WZ crystal phase, μ X cancels out and thus, the conclusions do not depend on its exact value, as already shown in refs , . The same happens when comparing the formation energy of a dopant in the neutral and singly charged state, which determines the transition energy (neither the transition energy depends on μ X ).…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…, ref for a discussion of the case of H in SiC). Notice, however, that whenever we compare the formation energy of a given impurity in the ZB or WZ crystal phase, μ X cancels out and thus, the conclusions do not depend on its exact value, as already shown in refs , . The same happens when comparing the formation energy of a dopant in the neutral and singly charged state, which determines the transition energy (neither the transition energy depends on μ X ).…”
Section: Methodssupporting
confidence: 54%
“…The geometry of the doped supercells was optimized with a quasi-Newton algorithm until all the forces on the atoms were lower than 0.01 eV/Å. This computational setup proved to be accurate enough to give converged values of the formation energy, as shown in previous theoretical studies. …”
Section: Methodsmentioning
confidence: 86%
“…It will have great potential for innovative light sources implemented in MOEICs. In addition, it has been found that the group III dopant can be more easily introduced in the H–Ge due to the local C 3 v symmetry in comparison with the C–Ge. The H–Ge can even be stabilized by introducing carriers .…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism is related to the relaxation of momentum conservation law due to the spatial confinement and Heisenberg uncertainty principle, being dominant in both Si and Ge NCs, and the other mechanism is the inter-valley coupling between direct and indirect states induced by the interface of the NC with the embedding matrix 23 . Another way of bandgap tuning is by tailoring its level of directness, as recently demonstrated direct bandgap light emission in Ge and GeSi nanowires with hexagonal structure 5 , 24 , and GeSi quantum dots 25 and also by infrared detection extended to longer wavelengths in NCs of direct bandgap GeSn alloys 26 .…”
Section: Introductionmentioning
confidence: 99%